PWE-284 Khat as a possible cause of drug induced autoimmune hepatitis; a case series. (28th May 2012) - Riyaz, S; Imran, M; Karajeh, M
Abstract : Introduction: Khat is well recognised for its hepatotoxic effects. The exact mechanism by which it causes liver damage remains unknown. We report a series of patients with a history of khat use presenting with acute hepatitis, and review the potential role of khat in triggering auto immune hepatitis (AIH). Methods: The database at Sheffield Hospitals was searched for patients referred to the Hepatology department between 2005 and 2010 with liver problems and a history of khat use. They were then assessed for probability of having AIH using the revised criteria for diagnosis of AIH. 1 Results: Six patients presenting with acute hepatitis on a background of khat use were identified. All of the patients were male. Five of these patients were of Somali origin, while one patient was from Yemen. The age range of these patients was 24–57 years (mean 42.3 years). The patients were scored according to the revised autoimmune hepatitis criteria. They were given minus four (−4) for khat use on the scoring system due to its potential hepatotoxicity. Despite this, five out of six patients had a pre treatment score of 10 to 15 which placed them in the probable group for autoimmune hepatitis. The five patients that were in the probable group had at least a partial response to corticosteroids with a greater than 50% reduction in their ALT after 1-month of treatment. The patient that had scored negative for AIH (<10) showed the least improvement with prednisolone and continued to have raised liver enzymes after 1-year of treatment. Conclusion: The exact mechanism by which khat causes hepatotoxicity remains elusive. One possibility could be by triggering autoimmune hepatitis in a genetically susceptible individual. Further studies are needed to evaluate this phenomenon. 2 3 Competing interests: None declared. References: 1. Alvarez F, et al. International Autoimmune Hepatitis Group Report: review of criteria for diagnosis of autoimmune hepatitis. J Hepatol 1999;31 :929–38. 2. Chapman MH, Kajihara M, Borges G, et al. Severe, acute liver injury and khat leaves. N Engl J Med 2010;362 :1642–4. 3. Peevers CG, Moorghen M, Collins PL, et al. Liver disease and cirrhosis because of Khat chewing in UK Somali men: a case series. Liver Int 2010.